Yield Management application management capabilities at the restaurant "La Campana de Toledo" - Betancourt García, María Elena (2015)
Yield Management , whose main objective is the optimization of price and ability to maximize profit , shown as a key instrument in making pricing decisionsAs a result of the application at the restaurant " La Campana de Toledo " belonging to the Branch Extrahotelera Palmares Camaguey Cuba , its viability and importance for raising the utilization of installed capacity and economic efficiency of the company was shown Analyze the possibilities and the need to use the Yield Management in restaurants and steps to implement this tool in determining the optimal price and capabilities , with the use ofArtificial Neural Networks (ANN ) are left raised.